2021
DOI: 10.1007/s12355-021-00998-0
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Breeding in Reunion: Challenges, Achievements and Future Prospects

Abstract: All over the world, sugarcane breeding programs are developing new, high-yielding cultivars that are resistant to major diseases to improve the profitability and sustainability of the sugar-energy industries they serve. In Reunion Island, sugarcane genetic improvement efforts began in 1929. Many challenges had to be overcome. Continuous breeding efforts have been made to develop varietal resistances to control some major diseases and are still going on today. Given the extreme agroclimatic diversity that chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The first two sites (ES and GL) were representative of the irrigated coastal areas of the dry leeward coast of the island, and the three others were representative of the wet windward coast, either near sea level (LM, SB) or in the highlands (MC). Guilly et al (2017) and Dumont et al (2022) reported precise localization, climate and soil characteristics, and selection focus of each of these sites. The five sites were characterized by wet summers (November-April) and more or less dry winters (June-September).…”
Section: Experimental Sitesmentioning
confidence: 99%
See 4 more Smart Citations
“…The first two sites (ES and GL) were representative of the irrigated coastal areas of the dry leeward coast of the island, and the three others were representative of the wet windward coast, either near sea level (LM, SB) or in the highlands (MC). Guilly et al (2017) and Dumont et al (2022) reported precise localization, climate and soil characteristics, and selection focus of each of these sites. The five sites were characterized by wet summers (November-April) and more or less dry winters (June-September).…”
Section: Experimental Sitesmentioning
confidence: 99%
“…Breeding and selecting for resistant or tolerant varieties is all the more important because, although harvested annually, a sugarcane crop is established for several years (Van Dillewjin 1952). In Reunion, sugarcane fields are usually only replanted every 10 years (Dumont et al 2022). Therefore, the use of insufficiently resistant cultivars may result in recurrent economic losses for a long period.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations